ROZWÓJ ŚRODOWISKA INSTYTUCJONALNEGO W NOWYCH KRAJACH UNII EUROPEJSKIEJ PRZYPADEK ESTONII I POLSKI - Kowalski, Tadeusz; Wihlborg, Clas; Vensel, Vello (Wydział Prawa i Administracji UAM, 2007)
The aim o f the paper is to present the results of a series o f interviews and surveys carried out among Estonian and Polish managers in Estonia and Poland between 1997-2004. The survey was conducted in an attempt to quantify evolution and perception of the quality of the legal environment in those economies under transition, at the time when both states were preparing to accede to the European Union. The results o f that empirical study are presented against the background o f the literature on institutional aspects o f the economic transformation. The surveys are focused on three vital areas: the functioning of government agencies, or public institutions, the legislative procedures and law enforcement.
DEVELOPMENT OF THE INSTITUTIONAL ENVIRONMENT IN NEW EU MEMBER STATES ON THE EXAMPLE OF ESTONIA AND POLAND